Comparison of the Effectiveness of Permethrin 1% and Dimeticone 4% as Therapy of Pediculosis Capitis: Literature Review - Dwi Advina Herdiyanti; Listiana Masyita Dewi; Riandini Aisyah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: Pediculosis capitis is a scalp disease caused by the infestation of obligate ectoparasites. Infection is usually found in children aged 6-12 years, girls have a higher risk of infection than boys, especially in rural areas in developing countries. One example of treatment that can be done to treat Pediculosis capitis infection is the use of 1% permethrin or 4% dimeticone. Objective: The aim of this study was to compare the effectiveness of permethrin 1% and dimeticone 4% as a treatment for pediculosis capitis. Methods: The research method uses a literature review research design. The data in this study were obtained from several journal databases, namely PubMed, Google Scholar, and Research Gate with the keywords